Preparation method of superfine niobium oxide

By using ultrasonic dispersion and gelatin to fix the crystal nucleus during the preparation of niobium oxide, adjusting pH and refrigerating and standing, the agglomeration problem is solved, and the preparation of ultrafine niobium oxide is achieved, and a product with small particle size, narrow distribution and high purity is obtained.

CN119683682AActive Publication Date: 2025-03-25JIANGXI PROVINCE DING HAI TANTALUM & NIOBIUM

Patent Information

Application Number
CN202411839285.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-25
Estimated Expiration
2044-12-13

AI Technical Summary

Technical Problem

The existing niobium oxide preparation process is prone to agglomeration, resulting in excessive particle size or wide particle size distribution range, making it difficult to obtain an ideal particle size and a narrow particle size distribution range.

Method used

A preparation method of ultrafine niobium oxide is adopted. After mixing the fluoroniobate solution, aluminum salt solution and gelatin solution, dispersing it evenly, adjusting the pH to 9-10, refrigerate and letting it stand, dry, crush, calcin and pickling, to obtain ultrafine niobium oxide.

Benefits of technology

A superfine niobium oxide product with small particle size and narrow particle size distribution range is achieved, which avoids agglomeration and growth, and improves the purity and particle size uniformity of the product.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of powder metallurgy. More specifically, the invention relates to a preparation method of ultrafine niobium oxide. The preparation method comprises the following specific preparation steps: taking 90-100 parts by weight of gelatin solution with the mass fraction of 3-5%, 60-80 parts by weight of fluorine niobate solution with the mass fraction of 10-15% and 4-10 parts by weight of aluminum salt solution with the mass fraction of 3-6%; mixing the fluorine niobate solution, the aluminum salt solution and the gelatin solution, and ultrasonically dispersing uniformly to obtain a mixed solution; dropwise adding a precipitant into the mixed solution in a stirring state to adjust the pH value to 9-10, continuously stirring and reacting, refrigerating and standing for 24-56 hours at the temperature of 2-6 DEG C, drying and crushing to obtain a crushed material; calcining the crushed material in an air atmosphere, and then cooling and scattering to obtain a calcined material; and pickling the obtained calcined material with hydrochloric acid, washing with water, and drying to obtain the ultrafine niobium oxide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of powder metallurgy and more specifically relates to a method for preparing ultrafine niobium oxide. Background Art

[0002] As an important electronic material, niobium pentoxide has been widely used in ceramic capacitors, piezoelectric ceramics, thick film capacitors, dielectric materials, magnetic materials, optical materials and other fields. Although the total amount is not large, its growth in quantity and expansion in the industry are very rapid. Among them, niobium pentoxide used in capacitors occupies a large part, because adding niobium pentoxide can greatly improve the thermal stability of capacitors, and at the same time obtain a stable and high dielectric constant.

[0003] Generally speaking, for high-quality targets, firstly, they are required to have a high density (≥99.5%) and a high purity (≥99.99%); secondly, they are required to have a good microscopic phase structure, that is, the particle size of the target crystals is at the micron level and is evenly distributed. In addition, niobium pentoxide targets also need to have good mechanical properties. One of the keys to preparing high-quality niobium pentoxide targets lies in the physical parameters such as particle size, dispersibility and purity of niobium pentoxide powder. At present, the preparation of niobium pentoxide powder mostly uses fluoroniobic acid as raw materials. After precipitation reaction, the resulting precursor niobium hydroxide contains a large amount of inorganic anions such as fluoride ions, chloride ions and sulfate ions, which requires a large amount of pure water to wash, and it is not easy to wash.

[0004] Based on this, how to develop a method for preparing ultrafine niobium oxide to solve the above technical difficulties is one of the technical problems still faced by those skilled in the art. Summary of the invention

[0005] The technical problem to be solved by the present invention is: in view of the problem that agglomeration is easily occurred in the existing niobium oxide preparation process, resulting in the final product having a particle size that is too large, or a wide particle size distribution range, making it difficult to obtain an ideal particle size, and a narrow particle size distribution range, a method for preparing ultrafine niobium oxide is provided.

[0006] The purpose of the present invention is to provide a method for preparing ultrafine niobium oxide.

[0007] The above-mentioned purpose of the present invention is achieved through the following technical solutions:

[0008] A method for preparing ultrafine niobium oxide, the specific preparation steps comprising:

[0009] By weight, take 90-100 parts of a gelatin solution with a mass fraction of 3-5%, 60-80 parts of a fluoroniobate solution with a mass fraction of 10-15%, and 4-10 parts of an aluminum salt solution with a mass fraction of 3-6%;

[0010] The fluoroniobate solution, the aluminum salt solution and the gelatin solution are mixed and then dispersed uniformly by ultrasonication to obtain a mixed solution;

[0011] Under stirring, a precipitant is added dropwise to the mixed solution to adjust the pH to 9-10, and the mixture is stirred for reaction. After being refrigerated and allowed to stand for 24-56 hours at a temperature of 2-6° C., the mixture is dried and crushed to obtain a crushed material;

[0012] The crushed material is calcined in an air atmosphere, and then cooled and broken up to obtain a calcined material;

[0013] The obtained calcined material is pickled with hydrochloric acid, washed with water and dried to obtain ultrafine niobium oxide.

[0014] During the research, the inventors found that when the precipitant is added to the fluoroniobate solution, when the concentration of niobium hydroxide formed exceeds the solubility product under the condition, the ions gradually form crystal nuclei through mutual collision, and after the crystal nuclei are formed, the crystal nucleus ions in the solution diffuse to the surface of the crystal nucleus, thereby causing the crystal nucleus to gradually grow and form precipitation particles. Based on this, the inventors selected trivalent aluminum salt and fluoroniobate as a compound system. After the precipitant is added, the two can instantly form a large number of crystal nuclei. At this time, under the action of gelatin, once a crystal nucleus is generated, it can be adsorbed and fixed, thereby gradually forming a loose precipitate. Specifically, niobium ions are pentavalent and aluminum ions are trivalent. Compared with conventional monovalent or divalent metal ions, when they form hydroxide precipitates, they need to combine with more hydroxide ions. Therefore, in the process of further directional arrangement of the two on the basis of forming crystal nuclei to form precipitates, they are limited by the slow directional arrangement speed. Therefore, the two can gradually form loose precipitates that pile up on each other under the adsorption of gelatin;

[0015] As the reaction proceeds, the temperature is lowered to 2-6°C, and the gelatin begins to gradually gel, thereby fixing the loose precipitate produced by the reaction and avoiding excessive agglomeration and sedimentation. In the subsequent calcination process, the hydroxide can be dehydrated to gradually form niobium oxide and aluminum oxide, while the gelatin is converted into carbon dioxide and water when calcined in the air and can be removed smoothly without adversely affecting the purity of the product. The presence of aluminum oxide can also prevent niobium oxide from agglomerating with each other during high-temperature calcination to a certain extent. Although aluminum oxide can agglomerate with niobium oxide to a certain extent, in the final pickling process, the acid can dissolve aluminum oxide but cannot dissolve niobium oxide, thereby niobium oxide can be purified. More importantly, the presence of the aforementioned loose precipitate provides a channel for the acid to diffuse and penetrate smoothly into the interior during the subsequent pickling process. When aluminum oxide is dissolved, the niobium oxide around it naturally dissociates, and the niobium oxide that aggregates with aluminum oxide during the calcination process is dissolved again, thereby obtaining a pure ultrafine niobium oxide product with a small particle size and a narrow particle size distribution range.

[0016] Furthermore, the isoelectric point of the gelatin is ≤7.

[0017] For gelatin, its molecular structure contains both amino and carboxyl groups. On the basis of the above-mentioned technical solution, during the process of adjusting the pH to 9-10, the hydroxide ions ionized in the solution can ionize the carboxyl groups in the gelatin molecular structure and carry a negative charge. As a result, the gelatin molecules repel each other due to the same charges and the molecular chains stretch. In addition, the negatively charged carboxyl groups can adsorb niobium ions and aluminum ions in the system. In this way, once a crystal nucleus is formed, it can be quickly adsorbed and fixed to avoid further aggregation and growth of the crystal nucleus.

[0018] Further, the fluoroniobate is selected from any one of potassium fluoroniobate and sodium fluoroniobate;

[0019] The aluminum salt is selected from any one of aluminum nitrate, aluminum chloride and aluminum sulfate.

[0020] Furthermore, the precipitant is prepared by compounding ammonia water and ammonium bicarbonate in a mass ratio of 1:1; wherein the mass fraction of the ammonia water is 8-10%, and the mass fraction of the ammonium bicarbonate solution is 2-6%.

[0021] The further selection of weakly alkaline ammonia water and ammonium bicarbonate as a precipitant system is mainly because, when the two are ionized in an aqueous solution, the hydroxide ion concentration will not be too high instantly, resulting in instantaneous precipitation explosion. In addition, the presence of ammonium bicarbonate can produce carbon dioxide gas during the reaction. Under the action of carbon dioxide gas, the stretching of gelatin molecular chains can become smoother, which is more conducive to the formation of loose structure precipitates. The looser the structure, the more conducive it will be for the acid to diffuse and penetrate into the interior during the subsequent reaction.

[0022] Furthermore, the calcining of the crushed material in an air atmosphere comprises: transferring the crushed material into a muffle furnace, heating the crushed material to 550-600° C. at a rate of 2-5° C. / min in an air atmosphere, and calcining the crushed material for 4-6 hours.

[0023] Further, the step of pickling the calcined material with hydrochloric acid comprises:

[0024] The calcined material and a hydrochloric acid solution with a mass fraction of 10-15% are mixed in a mass ratio of 1:10-12;

[0025] Under the conditions of ultrasonic frequency of 200-250kHz and temperature of 40-60°C, ultrasonic acid washing is continuously performed for 4-6 hours, and then the filter cake is filtered and collected to obtain an acid-washed filter cake.

[0026] Furthermore, the specific preparation steps also include:

[0027] By weight, 90-100 parts of a gelatin solution with a mass fraction of 3-5%, 60-80 parts of a fluoroniobate solution with a mass fraction of 10-15%, 4-10 parts of an aluminum salt solution with a mass fraction of 3-6%, and 0.6-0.8 parts of nano-graphene oxide are taken;

[0028] After mixing the fluoroniobate solution, the aluminum salt solution, the gelatin solution and the nano-graphene oxide, the mixture is ultrasonically dispersed for 20-40 minutes at an ultrasonic frequency of 250-300 kHz to obtain a mixed solution;

[0029] Under stirring, a precipitant is added dropwise to the mixed solution to adjust the pH to 9-10, and the mixture is stirred for reaction. After being refrigerated and allowed to stand for 24-56 hours at a temperature of 2-6° C., the mixture is dried and crushed to obtain a crushed material;

[0030] The crushed material is calcined in an air atmosphere, and then cooled and broken up to obtain a calcined material;

[0031] The obtained calcined material is pickled with hydrochloric acid, washed with water and dried to obtain ultrafine niobium oxide.

[0032] Furthermore, the D50 of the nano-graphene oxide is 60-80nm.

[0033] The inventors further discovered that if a certain amount of nano-sized graphene oxide is added to the system, under ultrasonic treatment conditions of 250-300kHz, the lamellar structure can be gradually peeled off to form a single-layer structure, thereby fully exposing polar functional groups such as carboxyl, hydroxyl and epoxy groups in the graphene oxide structure, and these functional groups can form hydrogen bonding forces with gelatin. In this way, during the formation of loose precipitates, the single-layer graphene oxide can be embedded in its loose structure. During the calcination process, the graphene oxide is essentially carbon, which can also be removed with the calcination in the air atmosphere. In this process, heat can be quickly transferred to accelerate the calcination efficiency. At the same time, and more importantly, after it is removed, the precipitate adsorbed on its surface can also be dissociated, thereby forming ultrafine-sized niobium oxide. DETAILED DESCRIPTION

[0034] The present invention is further described below with reference to specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0035] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.

[0036] Example 1

[0037] By weight, 90 parts of a 3% gelatin solution, 60 parts of a 10% fluoroniobate solution, 4 parts of a 3% aluminum salt solution, and 0.6 parts of nano-graphene oxide are taken;

[0038] The D50 of the nano graphene oxide is 60nm;

[0039] The isoelectric point of the gelatin is 6.8;

[0040] The fluoroniobate is selected from potassium fluoroniobate;

[0041] The aluminum salt is selected from aluminum nitrate;

[0042] The precipitant is prepared by mixing ammonia water and ammonium bicarbonate in a mass ratio of 1:1; wherein the mass fraction of the ammonia water is 8%, and the mass fraction of the ammonium bicarbonate solution is 2%;

[0043] After mixing the fluoroniobate solution, the aluminum salt solution, the gelatin solution and the nano-graphene oxide, the mixture was ultrasonically dispersed for 20 minutes at room temperature and an ultrasonic frequency of 250 kHz to obtain a mixed solution;

[0044] Under the stirring state of 300 r / min, the precipitant is added dropwise to the mixed solution at a rate of 8 mL / min to adjust the pH to 9. After the reaction is completed, the mixture is stirred at 200 r / min for 40 min with a stirrer, and then the mixture is refrigerated and allowed to stand for 24 h at 2° C., and then vacuum freeze-dried to obtain dry materials. The dried materials are then crushed and passed through a 400-mesh sieve to obtain crushed materials.

[0045] The crushed material was transferred into a muffle furnace, heated to 550°C at a rate of 2°C / min in an air atmosphere, kept at this temperature for 6 hours, cooled to room temperature with the furnace, and broken up to obtain a calcined material;

[0046] The calcined material and a 10% hydrochloric acid solution are mixed in a mass ratio of 1:10;

[0047] Under the conditions of ultrasonic frequency of 200kHz and temperature of 40°C, ultrasonic pickling is continuously carried out for 4 hours, and then the filter cake is filtered and collected to obtain a pickling filter cake. The pickling filter cake is then washed with water until the washing liquid becomes neutral and dried to obtain ultrafine niobium oxide.

[0048] Example 2

[0049] By weight, 95 parts of a 4% gelatin solution, 70 parts of a 12% fluoroniobate solution, 6 parts of a 5% aluminum salt solution, and 0.7 parts of nano-graphene oxide are taken;

[0050] The D50 of the nano graphene oxide is 70nm;

[0051] The isoelectric point of the gelatin is 6.6;

[0052] The fluoroniobate is selected from sodium fluoroniobate;

[0053] The aluminum salt is selected from aluminum chloride;

[0054] The precipitant is prepared by mixing ammonia water and ammonium bicarbonate in a mass ratio of 1:1; wherein the mass fraction of the ammonia water is 9%, and the mass fraction of the ammonium bicarbonate solution is 4%;

[0055] After mixing the fluoroniobate solution, the aluminum salt solution, the gelatin solution and the nano-graphene oxide, the mixture was ultrasonically dispersed for 30 minutes at room temperature and an ultrasonic frequency of 280 kHz to obtain a mixed solution;

[0056] Under the stirring state of 300 r / min, the precipitant is added dropwise to the mixed solution at a rate of 9 mL / min to adjust the pH to 9.5. After the reaction is completed, the mixture is stirred at 200 r / min with a stirrer for 50 min, and then refrigerated and allowed to stand for 48 h at a temperature of 4° C., and then vacuum freeze-dried to obtain dry materials, and then the dry materials are crushed and passed through a 400-mesh sieve to obtain crushed materials;

[0057] The crushed material was transferred into a muffle furnace, heated to 580°C at a rate of 3°C / min in an air atmosphere, kept at this temperature for calcination for 5 hours, cooled to room temperature with the furnace, and broken up to obtain a calcined material;

[0058] The calcined material and a 12% hydrochloric acid solution are mixed in a mass ratio of 1:11;

[0059] At an ultrasonic frequency of 220 kHz and a temperature of 50° C., the ultrasonic pickling is continued for 5 hours under heat preservation, and then the filter cake is filtered and collected to obtain an acid-washed filter cake. The acid-washed filter cake is then washed with water until the washing liquid becomes neutral and dried to obtain ultrafine niobium oxide.

[0060] Example 3

[0061] By weight, 100 parts of a 5% gelatin solution, 80 parts of a 15% fluoroniobate solution, 10 parts of a 6% aluminum salt solution, and 0.8 parts of nano-graphene oxide are taken;

[0062] The D50 of the nano graphene oxide is 80nm;

[0063] The isoelectric point of the gelatin is 6.5;

[0064] The fluoroniobate is selected from potassium fluoroniobate;

[0065] The aluminum salt is selected from aluminum sulfate.

[0066] The precipitant is prepared by mixing ammonia water and ammonium bicarbonate in a mass ratio of 1:1; wherein the mass fraction of the ammonia water is 10%, and the mass fraction of the ammonium bicarbonate solution is 6%;

[0067] After mixing the fluoroniobate solution, the aluminum salt solution, the gelatin solution and the nano-graphene oxide, the mixture was ultrasonically dispersed for 40 minutes at room temperature and an ultrasonic frequency of 300 kHz to obtain a mixed solution;

[0068] Under the stirring state of 300 r / min, the precipitant is added dropwise to the mixed solution at a rate of 10 mL / min to adjust the pH to 10. After the reaction is completed, the mixture is stirred at 200 r / min for 60 min with a stirrer, and then the mixture is refrigerated and allowed to stand for 56 h at 6° C., and then vacuum freeze-dried to obtain dry materials. The dried materials are then crushed and passed through a 400-mesh sieve to obtain crushed materials.

[0069] The crushed material was transferred into a muffle furnace, heated to 600°C at a rate of 5°C / min in an air atmosphere, kept at this temperature for 4 hours, cooled to room temperature with the furnace, and broken up to obtain a calcined material;

[0070] The calcined material and a 15% hydrochloric acid solution are mixed in a mass ratio of 1:12;

[0071] At an ultrasonic frequency of 250 kHz and a temperature of 60° C., the ultrasonic pickling is continued for 6 hours, and then the filter cake is filtered and collected to obtain an acid-washed filter cake. The acid-washed filter cake is then washed with water until the washing liquid becomes neutral and dried to obtain ultrafine niobium oxide.

[0072] Example 4

[0073] The present embodiment differs from the embodiment 1 in that no nano-graphene oxide is added, and the other conditions remain unchanged.

[0074] Example 5

[0075] Compared with Example 1, this embodiment is different in that:

[0076] After mixing the fluoroniobate solution, the aluminum salt solution, the gelatin solution and the nano-graphene oxide, the mixture was ultrasonically dispersed for 40 minutes at room temperature and an ultrasonic frequency of 80 kHz to obtain a mixed solution;

[0077] The rest of the conditions remain unchanged.

[0078] Example 6

[0079] Compared with Example 1, this embodiment differs in that the precipitant is ammonia water, no ammonium bicarbonate solution is added, and the other conditions remain unchanged.

[0080] Comparative Example 1

[0081] The difference between this comparative example and Example 1 is that a polyvinyl alcohol solution with a mass fraction of 3% is used to replace the gelatin solution, and other conditions remain unchanged.

[0082] Comparative Example 2

[0083] The difference between this comparative example and Example 1 is that an equal mass of deionized water is used to replace the aluminum salt solution, and other conditions remain unchanged.

[0084] The products obtained in the above embodiments and comparative examples were tested for particle size using a laser particle size analyzer to obtain the D50 and particle size distribution range of the products respectively;

[0085] The obtained product was analyzed for impurities by chemical analysis and atomic spectroscopy to obtain the purity of the product, as shown in Table 1;

[0086] Table 1: Product test results

[0087] D50 / μm Particle size distribution / μm purity / % Example 1 0.12 0.03-0.26 99.5 Example 2 0.13 0.02-0.24 99.6 Example 3 0.11 0.02-0.22 99.5 Example 4 0.18 0.01-0.35 99.6 Example 5 0.16 0.01-0.32 99.4 Example 6 0.15 0.02-0.30 99.3 Comparative Example 1 0.25 0.01-0.55 99.1 Comparative Example 2 0.20 0.01-0.40 99.4

[0088] It can be seen from the test results in Table 1 that the product obtained by the present invention has a smaller particle size, a narrow particle size distribution range, and the purity of the product can also be guaranteed.

[0089] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing ultrafine niobium oxide, characterized in that: The specific preparation steps include: By weight, take 90-100 parts of a gelatin solution with a mass fraction of 3-5%, 60-80 parts of a fluoroniobate solution with a mass fraction of 10-15%, and 4-10 parts of an aluminum salt solution with a mass fraction of 3-6%; The fluoroniobate solution, the aluminum salt solution and the gelatin solution are mixed and then dispersed uniformly by ultrasonication to obtain a mixed solution; Under stirring, a precipitant is added dropwise to the mixed solution to adjust the pH to 9-10, and the mixture is stirred for reaction. After being refrigerated and allowed to stand for 24-56 hours at a temperature of 2-6° C., the mixture is dried and crushed to obtain a crushed material; The crushed material is calcined in an air atmosphere, and then cooled and broken up to obtain a calcined material; The obtained calcined material is pickled with hydrochloric acid, washed with water and dried to obtain ultrafine niobium oxide.

2. The method for preparing ultrafine niobium oxide according to claim 1, characterized in that: The isoelectric point of the gelatin is ≤7.

3. The method for preparing ultrafine niobium oxide according to claim 1, characterized in that: The fluoroniobate is selected from any one of potassium fluoroniobate and sodium fluoroniobate; The aluminum salt is selected from any one of aluminum nitrate, aluminum chloride and aluminum sulfate.

4. The method for preparing ultrafine niobium oxide according to claim 1, characterized in that: The precipitant is prepared by mixing ammonia water and ammonium bicarbonate in a mass ratio of 1:1; wherein the mass fraction of the ammonia water is 8-10%, and the mass fraction of the ammonium bicarbonate solution is 2-6%.

5. The method for preparing ultrafine niobium oxide according to claim 1, characterized in that: The calcining of the crushed material in an air atmosphere comprises: transferring the crushed material into a muffle furnace, heating the crushed material to 550-600° C. at a rate of 2-5° C. / min in an air atmosphere, and calcining the crushed material for 4-6 hours.

6. The method for preparing ultrafine niobium oxide according to claim 1, characterized in that: The step of pickling the calcined material with hydrochloric acid comprises: The calcined material and a hydrochloric acid solution with a mass fraction of 10-15% are mixed in a mass ratio of 1:10-12; Under the conditions of ultrasonic frequency of 200-250kHz and temperature of 40-60°C, ultrasonic acid washing is continuously performed for 4-6 hours, and then the filter cake is filtered and collected to obtain an acid-washed filter cake.

7. The method for preparing ultrafine niobium oxide according to claim 1, characterized in that: The specific preparation steps also include: By weight, 90-100 parts of a gelatin solution with a mass fraction of 3-5%, 60-80 parts of a fluoroniobate solution with a mass fraction of 10-15%, 4-10 parts of an aluminum salt solution with a mass fraction of 3-6%, and 0.6-0.8 parts of nano-graphene oxide are taken; After mixing the fluoroniobate solution, the aluminum salt solution, the gelatin solution and the nano-graphene oxide, the mixture is ultrasonically dispersed for 20-40 minutes at an ultrasonic frequency of 250-300 kHz to obtain a mixed solution; Under stirring, a precipitant is added dropwise to the mixed solution to adjust the pH to 9-10, and the mixture is stirred for reaction. After being refrigerated and allowed to stand for 24-56 hours at a temperature of 2-6° C., the mixture is dried and crushed to obtain a crushed material; The crushed material is calcined in an air atmosphere, and then cooled and broken up to obtain a calcined material; The obtained calcined material is pickled with hydrochloric acid, washed with water and dried to obtain ultrafine niobium oxide.

8. The method for preparing ultrafine niobium oxide according to claim 7, characterized in that: The D50 of the nano graphene oxide is 60-80nm.

Citation Information

Patent Citations

  • Method for synthesizing graphene employing solid-phase calcination

    CN104773727A

  • Method for preparing rare earth-based crystal polishing powder

    CN108929634A

  • Low-temperature calcination process of superfine niobium oxide

    CN118307034A

  • Niobium oxide and its manufacturing method

    JP2004292234A

Cited By

  • Preparation method and application of chlorine-containing photocatalytic material

    CN121130921A

  • Preparation method and application of a chlorine-containing photocatalytic material

    CN121130921B